Gracilis muscles as neoanal spinchter for faecal incontinence - MH, Zailani; Md Nor, Azmi; KI, Deen (2010)
Faecal incontinence is a debilitating chronic clinical condition which may affect the patient and care givers. Modality of treatment is based on severity of the symptoms as well as the anatomical defect itself, availability of resources and expertise. We describe a modified technique of dynamic graciloplasty as neoanal sphincter for the treatment severe faecal incontinence who has failed previous over lapping sphincteroplasty. In our modified version, instead of using implanted intramuscular electrodes and subcutaneous neurostimulator to provide continuous stimulation, the patient will undergo an external stimulation on the nerve of transplanted gracilis periodically and concurrent biofeedback therapy. We believe the technique is relatively easy to learn and very cost effective without any electrodes or neurostimulator related complications